PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA PENCUCIAN UANG YANG DILAKUKAN OLEH KORPORASI SEBAGAI SUBJEK HUKUM - Busri, Ihsan; Multiwijaya, Vience Ratna; Suar, Aprima (Ensiklopedia of Journal, 2024)
Abstract: Money laundering carried out by corporations is an illegal act that involves a series of activities to disguise the origin of funds obtained from criminal activities, with the aim of making the funds appear legitimate and legal. Corporations in money laundering crimes are involved as entities that facilitate the money laundering process, either through business transactions, transfer of assets, or the use of non-transparent financial structures. This research examines how corporations can be responsible for criminal acts of money laundering according to Law no. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering (UU TPPU), as well as legal accountability policies for the corporations involved. The research method used is normative legal research, which focuses on analyzing legal norms related to corporate responsibility in money laundering crimes. The research results show that in the context of Indonesian law, corporations are recognized as legal subjects that can be held responsible for criminal acts of money laundering. Based on the TPPU Law, corporations can not only be made subject to responsibility for criminal acts of money laundering committed by individuals acting on behalf of or for the interests of the corporation, but can also be imposed on individuals whether they are legal entities or non-legal entities.Keywords: Corporations, Money Laundering Crimes and Criminal Responsibility